PENGARUH SOCIAL MEDIA MARKETING TERHADAP KESADARAN MEREK, CITRA MEREK DAN KEPUASAN KONSUMEN - Usman Wibowo, Didik; Yulianto, Edy; Sunarti, Sunarti (Profit: Jurnal Adminsitrasi Bisnis, 2022)
The purpose of this study was to determine the effect of social media marketing on brand awareness, brand image and consumer satisfaction of Samsung in Indonesia. The type of research used is Explanatory Research with a quantitative approach. In this study, the data used are primary data obtained and collected through direct surveys using questionnaires to respondents. Sampling in this study used the accidental sampling method with samples taken as many as 100 Instagram users who became followers of the Samsung Indonesia Instagram account who had become Samsung brand users. In analyzing the data in the study using SmartPLS. The results of this study: social media marketing has a significant effect on brand awareness, social media marketing has a significant effect on brand image, social media marketing has a significant effect on consumer satisfaction, brand awareness has a significant effect on brand image, brand awareness has a but not significant effect on consumer satisfaction, brand image has a significant effect on consumer satisfaction.